Summa theologica Halensis De legibus et praeceptis Lateinischer Text mit Übersetzung und Kommentar - Halesius , Alexander (Veröffentlichungen des Grabmann-Institutes zur Erforschung der mittelalterlichen Theologie und Philosophie, 2018)
So far, only the Latin text in a critical edition from the year 1948 has been available from the law treaty of the Summa Halensis. With the three-volume publication, a German translation and a commentary on this important work in the transition from early modern to high scholasticism will be presented together with the Latin text for the first time. From a conceptual point of view, this treatise was fundamental in its foundation and development of the different manifestations of the law - as eternal law, natural law, Mosaic law and evangelical law. His extensive interpretation of the Mosaic Law also has concrete references to the world of life and belief, which are revealing for the cultural and social history of this time. Also regarding the turning to the Torah in the current theology and in the context of the interreligious and socio-political discourses over the understanding of the law deserves attention the law council of the Summa Halensis, because he in many respects to the reflection over the function (s) of the law as well as the context of theology and law.